The Highs and the Lows of Construal Level Theory in the Community Rule from the Dead Sea Scrolls - Bach, Melissa Sayyad (Journal of Cognitive Historiography, 2022)
This article applies Construal Level Theory (CLT) on the ancient Jewish text the Community Rule (1QS), from the Dead Sea Scrolls. CLT, a theory developed within social and cognitive psychology, operates with the association between mental construals (high- or low-level) and psychological distance (spatial, temporal, social, or hypothetical). CLT proposes that the human mind’s ability to traverse the “here-and-now” is dependent on the interaction between levels of construal and psychological distance. High-level construals are abstract, general, and superordinate representations of things (i.e. the why, the end-state), while low-level construals are concrete, specific, and subordinate representations (i.e. the how, the means). Reading 1QS through the lens of CLT reveals one possible way in which this ancient text strives to persuade its potential recipients to act according to its ultimate goal by combining different modes of expression.